SENSITIVITY ANALYSIS OF CONCRETE PERFORMANCE USING FINITE ELEMENT APPROACH - Y. H. Parjoko (Journal of the Civil Engineering Forum, 2012)
This study aims to understand the effect of applying several parameters: different axle load configuration, concrete properties, subgrade properties, slab thickness, joint characteristics, shoulder construction, bounded HMA overlay on concrete pavement, and bounded and unbounded CTB foundation over subgrade on the fatigue and erosion related distresses in concrete pavements. KENSLAB, an elaborate finite element program is used to determine the concrete pavement responses: stresses and deflection under the defined parameters. The results obtained using this software is relatively close to known theoretical Westergaard solutions. Several other findings related to pavement performance and behavior are made through this study. Multiple axle configurations is less damaging than single axle configuration in terms of fatigue life. Increasing the thickness is very effective in reducing the edge stress. Using concrete with higher modulus of elasticity brings only a small increase to the edge stress. Increasing the slab thickness is the most effective way to increase the fatigue life. Increasing subgrade modulus is more effective in reducing corner deflection than decreasing edge stress. The availability of tied shoulder construction gives significant impact in both reducing edge stress and corner deflection. The debonding condition between layers has a significant effect on pavement responses. Keywords: Concrete pavement, fatigue failure, erosion failure, finite element, KENSLAB.